ARCHITECTURAL AND URBAN PLANNING PRINCIPLES OF CATERING SYSTEM ORGANIZATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The rapid mass growth of catering and wedding facilities is significant in the article. The number of new wedding halls, bars, cafes, clubs, coffee shops, and fast food companies that combine recreation in different ways is increasing day by day. The social direction of the market economy determines the need to qualitatively change the service sector, in particular, catering.